Quality of Care and Outcomes of Patients With Gynecologic Malignancies Treated at Safety-Net Hospitals. Issue 3 (7th June 2019) - Gamble, Charlotte R; Huang, Yongmei; Tergas, Ana I; Khoury-Collado, Fady; Hou, June Y; St. Clair, Caryn M; Ananth, Cande V; Neugut, Alfred I; Hershman, Dawn L; Wright, Jason D
Abstract: Background: Although safety-net hospitals (SNH) provide a valuable role serving vulnerable patients, the quality of gynecologic oncology care at these hospitals remains inadequately documented. We examined the quality of care at SNH for women with gynecologic cancers. Methods: We used the National Cancer Database to identify hospitals that treated patients with uterine, ovarian, or cervical cancer from 2004 to 2015. Hospitals with the greatest proportion of uninsured patients or Medicaid beneficiaries were defined as SNH. Quality metrics were derived from evidence-based recommendations. Thirty-day mortality, readmission rates, and 5-year survival were calculated. Multivariable models were developed to determine the association between treatment at SNH and outcomes. Results: Overall, 594 750 patients diagnosed with gynecologic cancer were treated at 1340 hospitals. Compared with non-SNH, patients at SNH were younger, more frequently racial minorities, low income, and had more aggressive histologies and advanced-stage tumors. SNH had lower rates of minimally invasive surgery for uterine cancer (62.3% vs 75.9%, P  <   .0001), debulking for ovarian cancer (83.6% vs 86.9%, P  <   .05), and lymph node assessment for all three cancer types ( P  <   .05). Rates of chemotherapy for uterine and ovarian cancer was greater whereas concurrent chemoradiation for cervical cancer was lower ( P  <   .05 for all). Thirty-day mortality and readmission rates were equivalent. Mortality was moderately worse for patients with stage IV ovarian cancer and stage II–III cervical cancer ( P  <   .05) but were otherwise equivalent. Conclusions: After adjusting for patient and tumor characteristics, women with gynecologic cancers treated at SNH receive lower-quality surgical care and equivalent medical care and a subset of these patients has modest decreases in survival.